Validity and reliability of the malay translated version of the cyberbullying scale among secondary school adolescents in Muar, Johor - Saman, Zaitun Mohd (2020)
Introduction: Cyberbullying gives negative impacts on adolescent and still under-reported in Malaysia. Cyberbullying Scale (CBS) is used to measure cyberbullying; nonetheless, due to the cultural, language and environmental differences between western and eastern population, the validity and reliability need to be established before it can be used. Objectives: To evaluate the validity and reliability of Cyberbullying Scale in Malay version (CBS-M) among secondary school students in Johor, as well as to determine the correlation with DASS-21 and Online Protection Behavior. Methods: This is a cross-sectional study which involved self-administered questionnaire was conducted in two phases, exploratory factor analysis (EFA) phase and confirmatory factor analysis (CFA) phase. Participants were recruited using a multistage cluster sampling method. Descriptive statistics, EFA and CFA and correlation analysis were applied by using RStudio Version 1.2.5033. Results: A total of 401 respondents participated in this study, EFA phase consisted 138 respondents and CFA phase consisted 263 respondents. For EFA phase, the majority of the respondents were female (65.9%) and Malay (89.9%). Results for EFA showed factor loading of all the items ranged from 0.3 to 0.7, and communalities ranged from 0.08 to 0.56. All items of CBS-M were remaining in the model during the EFA phase and the measuring reliability by Cronbach’s alpha was 0.87. CFA assessment reported the final model of CBS-M with a one factor model with all 14 items remaining, with the value of fit indices CFI = 0.946, TLI = 0.932, SRMR = 0.055 and RMSEA = 0.049. The fit indices were within the acceptable range. The composite reliability was 0.832. There was a significant positive correlation between CBS-M with stress, anxiety and depression. Conclusion: CBS-M consisted of one factor with 14 items and has good correlation with DASS-21. The questionnaire is a valid and reliable tool to be used among young adolescents in Malaysia.